Money Illusion and Coordination Failure - Ernst Fehr; Jean-Robert Tyran (Institute for the Study of Labor (IZA), 2004)
Economists long considered money illusion to be largely irrelevant. Here we show, however, that money illusion has powerful effects on equilibrium selection. If we represent payoffs in nominal terms, choices converge to the Pareto inefficient equilibrium; however, if we lift the veil of money by representing payoffs in real terms, the Pareto efficient equilibrium is selected. We also show that strategic uncertainty about the other players? behavior is key for the equilibrium selection effects of money illusion: even though money illusion vanishes over time if subjects are given learning opportunities in the context of an individual optimization problem, powerful and persistent effects of money illusion are found when strategic uncertainty prevails.
Keywords: E32; C9; E52; 330; money illusion; coordination failure; equilibrium selection; multiple equilibria; Geldillusion; Marktmechanismus; Gleichgewicht; Pareto-Optimum; Spieltheorie; Experiment